1999
DOI: 10.1093/emboj/18.12.3509
|View full text |Cite
|
Sign up to set email alerts
|

Progressive cis-inhibition of telomerase upon telomere elongation

Abstract: In yeast, the constant length of telomeric DNA results from a negative regulation of telomerase by the telomere itself. Here we follow the return to equilibrium of an abnormally shortened telomere. We observe that telomere elongation is restricted to a few base pairs per generation and that its rate decreases progressively with increasing telomere length. In contrast, in the absence of telomerase or in the presence of an overelongated telomere, the degradation rate linked to the succession of generations appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
238
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(270 citation statements)
references
References 77 publications
32
238
0
Order By: Relevance
“…The increased processivity requires Tel1. The telomere-shortening rate in the absence of telomerase is length-independent (Marcand et al 1999). The observed increased frequency of telomere elongation by telomerasewith telomere shortening is sufficient to explain telomere length homeostasis.…”
Section: Telomere Replicationmentioning
confidence: 91%
“…The increased processivity requires Tel1. The telomere-shortening rate in the absence of telomerase is length-independent (Marcand et al 1999). The observed increased frequency of telomere elongation by telomerasewith telomere shortening is sufficient to explain telomere length homeostasis.…”
Section: Telomere Replicationmentioning
confidence: 91%
“…Depletion of FEN1 appears to exacerbate telomere dysfunction by producing signal-free ends in fibroblasts (Saharia et al, 2008) and increasing the number of TIFs in ALT cells ( Figures 1d and e), thus leading to additional substrates capable of participating in end-to-end fusions. As telomerase acts on the shortest telomeres (Marcand et al, 1999;Forstemann et al, 2000;Ouellette et al, 2000), it would be recruited to those chromosome ends that experienced a catastrophic loss because of a stalled and unresolved replication fork or failure to cap the telomere. Telomerase could then extend the short telomeres, stabilizing them and rescuing telomere dysfunction.…”
Section: Role Of Fen1 In Alt Tumor Cells a Saharia And Sa Stewartmentioning
confidence: 99%
“…In an attempt to directly address whether Sba1p is required for telomere lengthening in vivo, we exploited an established system to determine the extension rates of a shortened telomere in WT and sba1⌬ yeast. In brief, the left arm terminus of chromosome VII contains an internal telomere tract that is flanked by Flp1p-recognition target (FRT) sites, the tract can be specifically removed upon the transient Flp1p expression and changes in length can be monitored during subsequent growth by Southern blot analysis (17,18). Using this system we determined the telomere extension rates in WT and sba1⌬ yeast and found that the sba1⌬ rate was 50% of WT after 3 generations and remained at 65% after 6 and 10 generations of growth (Fig.…”
Section: Fig 4 In Vivo Levels Of Sba1p Affect Telomere Occupancy Bymentioning
confidence: 99%